Ronald Story, Jonathan Edwards and the Gospel of Love - Huggins, Jonathan R. (Jonathan Edwards studies, 2013)
Ronald Story, Jonathan Edwards and the Gospel of Love. Amherst and Boston:University of Massachusetts Press, 2012. Pp. ix + 165. $22.95.